2019
DOI: 10.3390/genes10120990
|View full text |Cite
|
Sign up to set email alerts
|

Search for Ancestral Features in Genomes of Rhizobium leguminosarum bv. viciae Strains Isolated from the Relict Legume Vavilovia formosa

Abstract: Vavilovia formosa is a relict leguminous plant growing in hard-to-reach habitats in the rocky highlands of the Caucasus and Middle East, and it is considered as the putative closest living relative of the last common ancestor (LCA) of the Fabeae tribe. Symbionts of Vavilovia belonging to Rhizobium leguminosarum bv. viciae compose a discrete group that differs from the other strains, especially in the nucleotide sequences of the symbiotically specialised (sym) genes. Comparison of the genomes of Vavilovia strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
2
10
0
2
Order By: Relevance
“…In this report, with the help of group separation statistics, we demonstrated that intergroup divergence pertains to both gene categories ( Figure 5), although in hkg genes it is not pronounced enough to result in the emergence of new species. The last statement is also supported by the ANI statistics for Vaf genomes compared to Rlv, as reported by Chirak [46].…”
Section: Divergent Evolution Within R Leguminosarumsupporting
confidence: 67%
See 1 more Smart Citation
“…In this report, with the help of group separation statistics, we demonstrated that intergroup divergence pertains to both gene categories ( Figure 5), although in hkg genes it is not pronounced enough to result in the emergence of new species. The last statement is also supported by the ANI statistics for Vaf genomes compared to Rlv, as reported by Chirak [46].…”
Section: Divergent Evolution Within R Leguminosarumsupporting
confidence: 67%
“…Together with the proposed ancestral status of V. formosa, these data suggested that its strains might also preserve ancestral features, which were most clearly expressed at the level of concatenates of hkg and sym genes. Data indicating pronounced ancestral features for the sym gene arrangement within the bacterial genomes have been presented by Chirak et al [46].…”
Section: Evolutionary Status Of Symbionts Of V Formosamentioning
confidence: 80%
“…Recently, several published [ 21 , 50 , 52 ] and unpublished [ 53 ] studies have augmented the public databases with a large number of new genome sequences assigned to, or related to, R. leguminosarum . In addition, there have been numerous contributions of individual genomes [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Here, we examine this wealth of genomic information in order to establish whether R. leguminosarum , in the broad sense, is a distinct entity, and whether it can be subdivided into clearly defined groups that might, in future, be named as separate species within the overall R. leguminosarum species complex (Rlc).…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, we present a collection of new reviews and original research papers that target the genetic machinery behind the evolution of microbial symbioses, using both classical and novel experimental model systems. These include microbial symbioses with arthropod hosts [3][4][5], leguminous plants [6,7], social amoebae [8], and the largely understudied symbiosis of fungi in insects [9]. These papers provide key examples of current research on the microbial genetic repertoire (genes, genomic features, and their molecular evolution) and metabolic interactions (including biochemical and cellular mechanisms) involved in symbiotic interplay.…”
Section: Introductionmentioning
confidence: 99%